2016
DOI: 10.1111/jai.13059
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of reproduction and growth of the catfishIheringichthys labrosus(Lütken, 1874) after a reservoir formation

Abstract: Summary This work contributes to the knowledge of the reproduction, growth parameters and mortality rates of Iheringichthys labrosus in a newly‐formed reservoir. A total of 554 males and 1227 females were collected over 12 consecutive months, 1998–1999, from sites in the Corumbá Reservoir, Brazil, using gillnets (meshes: 2.4–16 cm). Information on each individual, i.e. standard length (cm), weight (g), sex, and gonadal development phase was recorded. The pectoral spines were removed to estimate age. The number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…The proportion of sex was skewed towards females, as they were larger than males, which accords with the findings of previous work on I. labrosus (Bazzoli et al, ; Holzbach et al, ; Soares de Santana et al, ; Suzuki et al, ) . This is probably attributable to sexual size dimorphism in this species.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The proportion of sex was skewed towards females, as they were larger than males, which accords with the findings of previous work on I. labrosus (Bazzoli et al, ; Holzbach et al, ; Soares de Santana et al, ; Suzuki et al, ) . This is probably attributable to sexual size dimorphism in this species.…”
Section: Discussionsupporting
confidence: 91%
“…Santana et al, 2016). In contrast, at higher latitude reproduction begins later (from September to December) such as at Furnas reservoir (20°40′S 46°19′W)(Bazzoli et al, 1997; Table 7,Figure 6).Consistently, Suzuki et al (2013) reported a later beginning of the reproduction (November to December), at southern location (22°39′S, 52°21′W).…”
mentioning
confidence: 78%
See 3 more Smart Citations